ANALISIS YURIDIS PENGINGKARAN WAKAF ATAS TANAH YANG SUDAH DIWAKAFKAN SECARA LISAN DITINJAU DARI FIQIH ISLAM DAN UNDANG-UNDANG NOMOR 41 TAHUN 2004 TENTANG WAKAF (STUDI KASUS KECAMATAN BATIN XXIV, KABUPATEN BATANG HARI, JAMBI) - EDI HENDRA (PREMISE LAW JURNAL, 2016)
DOSEN PEMBIMBING: 1. M. Hasballah Thaib 2. Muhd Yamin 3. Syahril Sofyan Wakaf (property donated for religious/community purposes) is a service to God with themotive of love to all human beings and helping other people. The property which has been donated will not belong to the benefactor anymore; it belongs to God (public) so that a wakaf land which has been donated cannot be sold, given, or inherited. In the Islamic fiqh, it is not difficult to make a wakaf valid: we only give it orally and the requirement for its validity is adequate. In Law No. 41/2004 on Wakaf, a pledge on wakaf is performed by Wakif to Nadzir before PPAIW to make it authentic. Nevertheless, up to the present, there have been many wakaf lands are sold or withdrawn by the benefactor or his heir since the donation is done orally and not embodied in AIW (Pledge on Wakaf Certificate) by PPAIW so that the land does not have law enforcement as what occurs in Batin XXIV Subdistrict, Batang Hari District, Jambi. Keywords        :           Denial on Wakaf Land, Oral Vow on Wakaf